RHYMING PROSE IN THE ENGLISH TRANSLATION OF SURAH AL-FATIHAH: A STUDY OF SHAWKAT M. TOORAWA’S APPROACH - Maulida Fitri Fi Ardillah; Asyiq Billah Ali; Muhammad Haris Miftah Sibawayhie; Fejrian Yazdajird Iwanebel (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
Shawkat M Toorawa is known for his innovative efforts in translating the Quran in English. He pays attention not only to the accuracy of meaning but also the aesthetic aspects such as rhyme and grammatical structure. In translating Surah Al Fatihah Toorawa managed to maintain rhyme consistently. The purpose of this study is to answer two academic problems namely to examine how Shawkat Toorawa maintains rhyming prose in his translation of Surah Al Fatihah and how Toorawa balances the aesthetic elements and syntactical conformity of the source text. This research uses the library research method by utilizing and synthesizing Shawkat Toorawas primary sources as well as some secondary writings that examine his thoughts. The results show that in translating Surah Al Fatihah Toorawa managed to balance the rhyming prose choose diction that has syllable stress uniformity and maintain the syntactic function of each word well. Sometimes he also made idiomatic transformations in his translation but he did not lose the essence of the verse. Toorawas innovation reflects an attempt to bring back the essence of the beauty of the musical resonance of the Quranic verse for non Arabic readers.